(untitled) (Journal of National Institute of Neurosciences Bangladesh, 2021)
Background: Extradural Haematoma can occur in different reasons. Objective: The purpose of the present study was to see the factors influencing the surgical outcomes of extradural haematoma. Methodology: This cross-sectional study was conducted in the Department of Neurosurgery at Dhaka Medical College Hospital, Dhaka, Bangladesh from January 2010 to June 2011 for a period of one year and six months. All patients presented with traumatic head injury having extradural haematoma in any age with both sexes who were underwent surgical or conservative management were selected as study population. The etiologies of head injuries were recorded. Result: Eighty (80) patients of traumatic head injury within and after 24 hours of head injury were enrolled in this study. In this study road traffic accident was the most common mode of injury which was 51(63.8%) cases followed by fall from height and assault which were 16(20.0%) cases and 13(16.2) cases respectively. Majority patients were recovered in good condition either surgery or conservative management which was 50(62.5%) cases. However, the moderate disability was reported in 17(21.2%) cases. Severe disability was found in 8(10.0%) cases. Persistent vegetative state was found in only 2 cases in conservative treatment. Death was found in 3(3.8%) cases. Conclusion: In conclusion road traffic accident is the most common mode of injury among the study population that causes extra dura haematoma which has the role as factors that influence the outcomes of the patients. Journal of National Institute of Neurosciences Bangladesh, January 2021, Vol. 7, No. 1, pp. 65-68